2007
DOI: 10.1007/s10775-007-9123-7
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of a relational cultural paradigm for vocational psychology

Abstract: An inclusive paradigm that emphasizes the nature and inevitable cultural shaping of meaning-making through relationships is represented as the relational cultural paradigm for vocational psychology presented in this article. This paradigm represents a phenomenological worldview or meta-theory for understanding meaning and mattering in worklife. The concept of worklife represents the nexus of work (unbound by dichotomous distinctions such as labour market and personal work), relationships, and culture (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 28 publications
4
74
0
Order By: Relevance
“…The results tentatively suggested that the adolescents described and presented their relationships as significant factors in their process of career and life-designing. Thus the results supported existing theories on relational aspects of career development (cf., Schultheiss, 2003Schultheiss, , 2007Savickas et al, 2009). The results also support Schultheiss's (2003Schultheiss's ( , 2007 view that the dimensions of selfregulation and relatedness are interconnected.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results tentatively suggested that the adolescents described and presented their relationships as significant factors in their process of career and life-designing. Thus the results supported existing theories on relational aspects of career development (cf., Schultheiss, 2003Schultheiss, , 2007Savickas et al, 2009). The results also support Schultheiss's (2003Schultheiss's ( , 2007 view that the dimensions of selfregulation and relatedness are interconnected.…”
Section: Discussionsupporting
confidence: 75%
“…These themes are seen as interconnected, not as opposite extremes of the same continuum. The interconnections have been widely discussed and studied in recent career counselling literature (Blustein, Schultheiss, & Flum, 2004;Hartung & Blustein, 2002;Phillips et al, 2001;Schultheiss, 2003Schultheiss, , 2007Schultheiss, Kress, Manzi, & Glasscock, 2001). According to Schultheiss (2003), the relational context may function as a positive resource but may contain hindrances or conflicts as well.…”
mentioning
confidence: 99%
“…Family culture and communication can therefore form an important element in vocational socialization (Jablin, 2001). Research has indeed highlighted that immediate and proximal reference groups such as the family have particular resonance for an individual's vocational identification and development (Brown, 2004;Schultheiss, 2007;Whiston & Keller, 2004).…”
Section: Literature Overview Callingsmentioning
confidence: 99%
“…It is hoped that the counseling for work and relationship perspective will contribute to the conversation in vocational psychology regarding the search for a new paradigm in response to the changing conditions of contemporary times (Collin & Young, 2000;Duarte, 2006, Savickas, 2000Schultheiss, 2007aSchultheiss, , 2007b. The notion of paradigm change is daunting.…”
mentioning
confidence: 99%